Feed People First: A Service Ecosystem Perspective on Innovative Food Waste Reduction. (February 2018) - Baron, Steve; Patterson, Anthony; Maull, Roger; Warnaby, Gary
Service research highlights the utility of adopting a service ecosystem approach to studying service innovation. It suggests that service innovations can arise from challenging and developing the institutions (i.e., norms, rules, practices, meanings, and symbols) which underpin an ecosystem. Also, recent emphasis on consumer well-being posits that studies of service provision to poor consumers are needed. Reflecting these research priorities, the context of this case study on service innovation is the food waste ecosystem, whereby service innovations can contribute to the alleviation of food poverty for thousands of citizens. The central actor of the ecosystem is the leading UK charity organization fighting food waste. The paper's contribution lies in using data from ecosystem actors to clarify the distinctions between institutions, thereby enhancing understanding of the application of institutional theory within the ecosystem and highlighting some theoretical implications for service innovation both within- and between-system levels. An actor institutions matrix is offered as a fruitful outcome of the analysis of the institutions, and suggested recommendations for operationalizing service ecosystem studies are outlined.